Highly Selective Optical Sensor Eu (TTA)3 Phen Embedded in Poly Methylmethacrylate for Assessment of Total Prostate Specific Antigen Tumor Marker in Male Serum Suffering Prostate Diseases - Garoub, Mohannad; Hefny, A. H.; Omer, W. E.; Elsaady, Mostafa M.; Abo-Aly, Mohamed M.; Sayqal, Ali A.; Alharbi, Ahmed; Hameed, Ahmed; Alessa, Hussain; Youssef, A. O.; Mohamed, Ekram H.; Gouda, Ayman A.; et al. (Frontiers in Chemistry, 2020)
A low-cost, simple, and highly selective method was used for the assessment of total prostate specific antigen (tPSA) in the serum of prostate cancer patients. This method is based on quenching the intensity of luminescence displayed by the optical sensor Eu (TTA)3 phen/poly methylmethacrylate (PMMA) thin membrane or film upon adding different concentrations of tPSA. The luminescent optical sensor was synthesized and characterized through absorption, emission, scanning electron microscopy (SEM), and x-ray diffraction (XRD), and is tailored to present red luminescence at 614 nm upon excitation at 395 nm in water. The fabricated sensor fluorescence intensity is quenched in the presence of tPSA in aqueous media. The fluorescence resonance energy transfer (FRET) is the main mechanism by which the sensor performs. The sensor was successfully utilized to estimate tPSA in the serum of patients suffering prostate cancer in a time and cost effective way. The statistical results of the method were satisfactory with 0.0469 ng mL−1 as a detection limit and 0.99 as a correlation coefficient.